Genetic characterization of Bhutanese native chickens based on an analysis of Red Junglefowl (Gallus gallus gallus and Gallus gallus spadecieus), domestic Southeast Asian and commercial chicken lines (Gallus gallus domesticus) - Dorji,Nedup (2012)
The genetic diversity of Bhutanese chickens needs to be understood in order to develop a suitable conservation strategy for these birds in Bhutan. In this, work, we used microsatellite markers to examine the genetic diversity of Bhutanese chickens. Four Bhutanese chicken varieties (Black plumage, Frizzle, Naked neck and Red Junglefowllike, corresponding to Yuebjha Narp, Phulom, Khuilay and Seim, respectively), two subspecies of Red Junglefowl (Gallus gallus gallus and Gallus gallus spadecieus), two varieties of Thai native chickens (Pradhu Hang Dam and Chee; Gallus gallus domesticus) representing the Southeast Asian domestic chicken, and two commercial lines (Broiler and Single Comb White Leghorn) were genotyped with 18 microsatellites that included 16 loci recommended by the FAO/ISAG for investigations of genetic variability in chickens. All loci were polymorphic, with the number of alleles ranging from six (MCW0111) to 23 (MCW0183). Substantial genetic variation was observed in all populations, with the Bhutanese native chicken Yuebjha Narp (Black plumage chicken) showing the lowest genetic variability. Despite extensive intrapopulation variation, the genetic differentiation among 10 populations was moderate. A neighbor-joining tree revealed the genetic relationships involved while principal component analysis showed that Bhutanese native chickens should be given priority in conservation efforts because of their genetic distinctiveness. Chee chickens are especially valuable as a reservoir of predomestic diversity, as indicated by their greater genetic variation and their position in the phylogenetic tree.